The role of non-hematopoietic stromal cells in the persistence of inflammation - Barone, Francesca; Nayar, Saba; Buckley, Chris (Frontiers in Immunology, 2013)
Inflammation results from the complex interaction between haematopoietic and stromal cells and growing evidence supports a key role for the stroma in driving the switch from acute resolving to persistence of chronic persistent inflammatory diseases. Stromal cells have also been shown to play a critical role in cancer biology, being involved in cancer growth, dissemination and inhibition of the autologous immune response, ultimately favouring persistence and metastatic spread. Similarly, blood and lymphatic endothelial cells contribute to tissue homeostasis during physiological inflammation but also lead to discorded leucocyte and tumour cell accumulation in pathological inflammation and cancer. This review aims to summarise the role that pathogenic stroma plays in the pathogenesis of diseases such as cancer and chronic inflammation.